Media Literacy: Smart in Making Islamic Content in Social Media in Sei Dadap District, Asahan District - Lakum , Lakum; Lubis, Nikmah; Hakim , Uky Firmansyah Rahman (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
The rapid development of media and communication technology requires audiences to have a number of knowledge and skills called media literacy, in order to use the media correctly. The main target is teenagers. Teenagers as active users of social media need to get attention in the use of social media. Teenagers are the age of self-discovery, high curiosity, and need various education that is used as a reference. But it is very unfortunate if a teenager abuses social media, accesses and consumes media content with various social activities from various Black Mail accounts that display pornographic content / posts, provocations, and many other things that are misused into adolescent consumption that is not appropriate for his age.To prevent these negative things, teenagers need to be equipped with journalistic knowledge so that they can create Islamic creative content as an adaptive step from the use of social media. This ability needs to be possessed by teenagers, especially teenagers from Sei Dadap District. The approach used is qualitative with a descriptive nature. The results showed that Media Literacy activities in Sei Dadap District had a positive impact so that teenagers were able to choose and choose good and true news. Then it is possible to create creative Islamic content on social media as an adaptive step from the use of social media. Creating creative Islamic content on social media is also a da'wah strategy that all social media users are capable of doing. The results of this study are expected to encourage further research in the form of elaboration of media literacy theories and concepts so that they can be translated into the Media Literacy Education curriculum. Â